COST BENEFITS ANALYSIS OF PH.D EDUCATION IN NIGERIA - ADU, Ebenezer Taiwo; AJAYI, Oyedokun Samuel (International Journal of Research -GRANTHAALAYAH, 2021)
This research work examined the cost benefits of Ph. D in Nigeria. It was a descriptive design of a survey type. The population of the study was all the lecturers and Ph. students of the University of Ado-Ekiti, Nigeria, 150 Lecturers and students were selected through simple random sampling and techniques. Two sets of research instruments were used one for the lecturers and the second one for the students currently undergoing Ph. . The validity of the instruments was done with the use of content, construct and face . Descriptive analysis was used to the data collected. The results showed that the cost of Ph. was higher compare to lower degrees, the prospect cadre for Ph. was high and that the financial and other benefits of Ph.D holders were higher than other degrees.